SYNTHESIS AND CHARACTERIZATION OF CARBOXYMETHYLATED CORNSTARCH - Zh.A. Nurakhmetova; E. P. Kurbashev; B.S. Selenova; T. Borke; V.O. Aseyev; S.E. Kudaibergenov (Academic Scientific Journal of Chemistry, 2019)
The aim of this study is preparation and characterization of carboxymethylated cornstarch (CMCS) for potential application as water based drilling fluids. The cornstarch was modified by sodium monochloroacetate. The structure of cornstarch and CMCS was established by H1 NMR and FTIR spectroscopy. The degree of carboxymethylation of cornstarch determined by H1 NMR spectroscopy was equal to 80%. The viscosity-average molecular weights (M) of pristine cornstarch and CMCS calculated from Mark-Kuhn-Houwink equation [ߟ=[KMa are equal to 2.15·103 gmol-1 and 2.75·105 gmol-1 respectively. The temperature dependent viscosity of CMCS was measured in water by Ubbelohde viscometer, while the rheological properties of CMCS in dependence of polymer concentration and ionic strength of the solution were evaluated by rheoviscometer. The thermal characteristics of samples were determined by differential scanning calorimeter (DSC) and thermogravimetric (TGA) and differential thermal analyzer (DTA). The morphological properties of cornstarch and CMCS were studied by scanning electron microscopy (SEM). The structural-mechanical, filtration and filter cake forming properties of drilling fluids and fluid loss indicators of CMCS were found